2009
DOI: 10.1016/j.juro.2009.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Transcutaneous Parasacral Electrical Stimulation for Overactive Bladder in Children: Long-Term Results

Abstract: Transcutaneous parasacral electrical stimulation is well tolerated, and demonstrates short and long-term effectiveness in treating overactive bladder in children. Symptoms eventually will recur in 10% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
19

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 22 publications
1
40
0
19
Order By: Relevance
“…Recently, supraspinal action of parasacral stimulation has been demonstrated [12]. Our previously published data demonstrate that TCPSE is effective in the treatment of OAB [8,9].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, supraspinal action of parasacral stimulation has been demonstrated [12]. Our previously published data demonstrate that TCPSE is effective in the treatment of OAB [8,9].…”
Section: Discussionmentioning
confidence: 93%
“…We showed that 63% of the patients symptomatically resolved completely and 20% improved significantly. In a long-term follow up, continued success was demonstrated in 84% for urgency, 74% for daytime incontinence and 78% for all daytime symptoms [9].…”
Section: Introductionmentioning
confidence: 86%
“…This variability translates into different approaches for defining the problem and even treatment modalities. Although behavioral modification remains the cornerstone of treatment, pharmacological and biofeedback techniques have been used (5).…”
Section: Introductionmentioning
confidence: 99%
“…Dans [7][8][9][10][11][12][13]. Dans notre étude, nous avons évalué l'efficacité sur le ressenti clinique du patient et sur le calendrier mictionnel.…”
Section: Discussionunclassified
“…Au cours des années 2000, quelques études ont rapporté des résultats encourageants chez l'enfant souffrant d'hyperactivité vésicale, avec une électrostimulation par voie transcutanée (électrodes de surface) au niveau du sacrum [7][8][9][10], ou par voie percutanée (introduction d'une aiguille) au niveau du nerf tibial [11][12][13]. Compte tenu du caractère « invasif » de la stimulation percutanée, et de l'efficacité démontrée chez l'adulte de la stimulation transcutanée, nous avons réalisé une étude évaluant l'efficacité et la tolérance de l'électrostimulation transcutanée transitoire du nerf tibial chez des patients âgés de moins de 15 ans pris en charge pour un syndrome clinique d'hyperactivité vésicale idiopathique réfractaire aux traitements préalables.…”
Section: Introductionunclassified